Ectopic Hamartomatous Thymoma: A Case Report and Literature Review - Yin, MD, PhD, Zhiwei; Zheng, MD, PhD, Ruifang; Cassano, MD, PhD, Charvi; Fidan-Ozbilgin, MD, Ozlem; Ahmed, MD, Shahida; Cai, MD, PhD, Donghong (North American Journal of Medicine and Science, 2018)
Ectopic hamartomatous thymoma is a rare benign tumor located at supraclavicular/suprasternal area and is speculated with a branchial anlage origin. There are usually 3 components in the tumor: spindle cells, epithelial cells, and adipose tissue, although proportion of each varies from case to case. The tumor cells present with a unique immunophenotype, with strong positivity for AE1/AE3, CD34, CD10, and variable staining for Bcl-2 and SMA. Here we report such a case in a 61 year old male, with a compatible morphology and immunopattern for this entity. [N A J Med Sci. 2018;11(1):11-14. DOI: 10.7156/najms.2018.110111]